A REVIEW OF THE NON-DEMARCATION BORDER COOPERATION BETWEEN INDONESIA AND MALAYSIA - Michelle Viandy Huang (Universitas Pelita Harapan, 2019)
Indonesia and Malaysia have established cooperation on various aspects of the border regions for decades. The two countries have ratified the 1984 Security Arrangement Treaty, where the General Border Committee (“GBC”) is established to contend the security aspect of the border areas. The GBC also formed a Social Economic Committee of Indonesia and Malaysia, which is called the SOSEKMALINDO, focusing on the social and economic aspects of the border. Meanwhile, there has been the 1970 Agreement on Border Trade (“BTA”) that governs the movement of goods in and out of the border and maintain the border’s economy. As time goes by, the border cooperation between the two countries has developed, resulting the need to meet the new challenges in terms of border security. While the governments have been emphasizing its focus on economic cooperation, the security challenges are neglected. Hence, this paper provides an analysis on the urgency to reform the 1984 Security Arrangement Treaty due to the overlapping function between the GBC and the BTA.BAHASA INDONESIA ABSTRAK: Indonesia dan Malaysia telah menjalin kerja sama dalam berbagai aspek wilayah perbatasan selama beberapa dekade. Misalnya, kedua negara telah meratifikasi Security Arrangement Treaty 1984, di mana General Border Committee (